The Gusjigang: Spiritual Entrepeneurship yang Mulai Luntur - Nazaruddin Latif, Nazaruddin Latif; Nurul Huda, Nurul Huda; Indarwati, Indarwati (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This article reviews Gujigang, a philosophy that has developed in Kudus Regency, especially in the western part. It is believed that this philosophy originates from Sunan Kudus, one of the propagators of Islam who is a member of Walisongo. In the early era, the emergence of this philosophy greatly influenced the spirit of developing the economy, thus creating a balance in the personality of economic actors. The balance is fulfilled in fulfilling the three interrelated indicators. A person can be classified as good if he has spiritual and economic qualities that can be fulfilled in a balanced way. By conducting qualitative research in which the data were obtained through observation and in-depth interviews, it was found that there was a paradigmatic shift among the people of Kudus Kulon. Part of the Kudus district which is close to the Kauman settlement. Borrowing from Cliffort Geertz's Studies, as students and at the same time priyayi, have a spiritual and economic balance. However, along with the times, business competition in the economic sector has become increasingly stringent, resulting in the punishment for the fading of the Gusjigang philosophy. The business of developing a pure economic business is just to get financial benefits that are not balanced with the spirit of fulfilling spiritual needs.